C-type natriuretic peptide and endothelium-dependent hyperpolarization in the guinea-pig carotid artery - Leuranguer, V (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: C-type natriuretic peptide (CNP) has been proposed to make a fundamental contribution in arterial endothelium-dependent hyperpolarization to acetylcholine. The present study was designed to address this hypothesis in the guinea-pig carotid artery. EXPERIMENTAL APPROACH: The membrane potential of vascular smooth muscle cells was recorded in isolated arteries with intracellular microelectrodes. KEY RESULTS: Acetylcholine induced endothelium-dependent hyperpolarizations in the presence or absence of N (G)-nitro-L-arginine, indomethacin and/or thiorphan, inhibitors of NO-synthases, cyclooxygenases or neutral endopeptidase, respectively. Acetycholine hyperpolarized smooth muscle cells in resting arteries and produced repolarizations in phenylephrine-stimulated arteries. CNP produced hyperpolarizations with variable amplitude. They were observed only in the presence of inhibitors of NO-synthases and cyclooxygenases and were endothelium-independent, maintained in phenylephrine-depolarized carotid arteries, and not affected by the additional presence of thiorphan. In arteries with endothelium, the hyperpolarizations produced by CNP were always significantly smaller than those induced by acetylcholine. Upon repeated administration, a significant tachyphylaxis of the hyperpolarizing effect of CNP was observed, while consecutive administration of acetycholine produced sustained responses. The hyperpolarizations evoked by acetylcholine were abolished by the combination of apamin plus charybdotoxin, but unaffected by glibenclamide or tertiapin. In contrast, CNP-induced hyperpolarizations were abolished by glibenclamide and unaffected by the combination of apamin plus charybdotoxin. CONCLUSIONS AND IMPLICATIONS: In the isolated carotid artery of the guinea-pig, CNP activates K(ATP) and is a weak hyperpolarizing agent. In this artery, the contribution of CNP to EDHF-mediated responses is unlikely.